Extent of the permissibility of partial rescission of the contract: - comparative study - Abed, Ali; Hasan, Jaleel (Journal of Legal Sciences, 2022)
In bilateral contracts, if one of the contracting parties does not fully perform his obligation the other contracting party may ask the court to rescission the contract in full, but the failure to perform may be limited to part of his obligation, then the following question arises: Can the contract be partially rescission ? It is noted that there is a great jurisprudential and judicial disagreement on this subject, And we ended up saying ​that it is not permissible for a court to order on partial rescission without the approval of the creditor, because the judgment of partial rescission requires to compel the creditor to accept partial payment, which is rejected under Article (392) of the Iraqi Civil law.